The effects of home country, gender and position on listening behaviors - Roebuck, D. B.; Bell, Reginald L.; Raina, Reeta; Lee, Cheng Ean Catherine * (Jordan Whitney, 2015)
Regardless of national culture, often listening is mentioned as an important component for effective business operations. In addition, understanding how individuals of different national cultures perceive and process listening is fundamental to our global world of work. The present study used Glenn and Pood (1989) Listening Self-Inventory to examine the distracted and attentive listening behaviors of male and female managers and non-managers who worked full time inthe countries of India, Malaysia, and the United States of America (USA). Findings in this study suggest USA females and males, in general, are less likely to be attentive listeners than the Indian and Malaysian respondents are. USA and Malaysian managers are less prone to be attentive listeners than non-managers while Indian managers are more likely to be attentive listeners. Regarding distracted listening behaviors, males are more prone to engage in distracted listening than females while managers are less likely to engage in distracted listening than non-managers. USA managers are more distracted in their listening than non-managers while Indian and Malaysian managers are less distracted listeners than the non-managers are. This study indicates differing national cultures, organizational position and gender can affect listening in the workplace.